PENYELIDIKAN TANAH MENGGUNAKAN METODE UJI SONDIR - Krisantos Ria Bela; Paulus Sianto (Eternitas: Jurnal Teknik Sipil, 2022)
Cone Penetration Test (CPT) or sondir is a method designed to determine and test the strength of the soil layer. This sondir test has been carried out in Tunfeu Village, Nekamese District, Kupang Regency, East Nusa Tenggara to determine the resulting bearing capacity and determine the type of foundation that is suitable for the research location point. The soil investigation method is carried out by direct testing in the field using a sondir tool. Secondary data were obtained from several literature studies. Primary data obtained from sondir results at three predetermined location points. Data analysis used two parameters at each depth, namely the Conus Resistance Value (qc) in kg/cm2, and the total shear value (Tf) in kg/cm units. The two parameters above were recorded for every 20 cm interval where at point 1 the value of qc ³ 245 kg/cm2 is obtained at a depth of –11.60 m with a Tf 337.33 kg/cm. At point 2 the value of qc ³ 225 kg/cm2 is obtained at a depth of –21.20 m with a Tf 394 kg/cm. While at point 3 the value of qc ³ 235 kg/cm2 is obtained at a depth of –19.60 m with a Tf 548.67 kg/cm. Based on the results of the sondir above, the type of foundation that is suitable for the soil conditions in Tunfeu Village is a pile or deep foundation (bored pile).